PERANCANGAN SISTEM INFORMASI PENGELOLAAN KEUANGAN PEMBANGUNAN DESA BERBASIS WEBSITE MENGGUNAKAN FRAMEWORK CODEIGNITER PADA DESA KEDUNG POMAHAN WETAN - Bagas Purbo Hantoro (2021)
In today's digital era, a lot of financial data is happening and there are also many different technologies. The use of information technology is a way of building village technology, especially in village finances in inputting financial data, storing and reporting financial. The existing system is still manual and uses software in the Microsoft Office Excel 2007 application. The purpose of this study is to make it easier for village treasurers to manage village development finances. This Financial Management Information System is designed using a codeigniter framework. Codeigniter uses the PHP programming language. To support this research, the method used in this study is the SDLC method (software development life cycle). The results of this study are to produce a Website-Based Village Development Financial Management Information System Design Using CodeIgniter Framework in Kedung Pomahan Wetan Village.